Identity Integration in Adolescents With Features of Gender Dysphoria Compared to Adolescents in General Population - Karvonen, Milla; Goth, Kirstin; Eloranta, Sami J.; Kaltiala, Riittakerttu (Frontiers in Psychiatry, 2022)
Adolescence is an important period for identity formation and identity consolidation is one of the main developmental tasks. Gender identity is an essential aspect of identity but so far little is known about its development. Neither has the identity development of adolescents with features of gender dysphoria (GD) been extensively studied so far. However, adolescents with features of GD have been shown to present extensive psychiatric psychopathology and could therefore be assumed also to have more problems with identity development. We set out to compare the identity integration of adolescents with features of GD (n=215; 186 natal females, 29 natal males) and adolescents from general population (n=400; 244 females, 154 males and 2 who did not report their sex) using a culture-adapted Finnish version of an assessment tool for adolescents and young adults on identity in terms of personality functioning, the Assessment of Identity Development in Adolescence (AIDA). AIDA is a 58-item self-report questionnaire enabling dimensional differentiation between healthy and impaired identity development. The continuous AIDA total score (sum score) and its subscales were analyzed using MANOVA, and dichotomized T-scores differentiating identity development in impaired and healthy range using cross-tabulations with chi-square statistics. Adolescents with features of GD showed identity development similar to adolescents in general population. The slight differences seen in AIDA scores were in favor of the GD group. The proportion scoring to identity impairment was lowest among gender-referred adolescents assigned males at birth. Identity integration of the gender-referred adolescents was further compared to that of 77 adolescents in specialist level psychiatric outpatient treatment (67 females, 10 males). The adolescent psychiatric outpatients scored much higher towards impaired identity on all AIDA scales than did the adolescents with features of GD. These results suggest that features of GD are not associated with problems in identity development in adolescents at large. Adolescents with features of GD may have been required to process their identity more, thereby advancing further in their identity consolidation process than young people on average.